Use of standard test organisms for sound validation of UV-based ballast water treatment systems. (July 2019) - Lundgreen, Kim; Holbech, Henrik; Pedersen, Knud Ladegaard; Petersen, Gitte Ingelise; Andreasen, Rune Røjgaard; George, Christaline; Drillet, Guillaume; Andersen, Martin
Abstract: To challenge ballast water treatment system (BWTS) efficacy for organisms in the size-class 10–50 μm, intake concentration during tests must reach certain minimum requirements. Often, natural concentrations are too low to meet intake requirements and standard test organisms (STOs) are added. We tested the robustness of Tetraselmis suecica and Odontella sp. to a range of UV-treatments to explore fluences needed to meet the IMO discharge standard (<10 org. ml −1 ) evaluated using two viability assessment methods. To meet discharge standards, fluences of >1000 mJ cm −2 were required using vital stain whereas 135–500 mJ cm −2 were needed using regrowth assays. Besides, results suggest that T. suecica and Odontella sp. were at least as robust as natural algae towards UV-treatments. We suggest the advantageous use of these species as STOs in test water to support intake water requirements and to obtain more conservative validation of UV-based BWTS to ensure more environmental protective procedures. Graphical abstract: Unlabelled Image Highlights: The use of standard test organisms for safer validation of UV-based BWTSs Higher robustness of STOs towards UV treatments compared to natural algae MPN method more suitable than vital stain method for validation of UV-based BWTS IMO intake concentration requirement can be fulfilled with standard test organisms.